2016
DOI: 10.1088/1748-0221/11/07/p07019
|View full text |Cite
|
Sign up to set email alerts
|

Results of the 2015 testbeam of a 180 nm AMS High-Voltage CMOS sensor prototype

Abstract: Active pixel sensors based on the High-Voltage CMOS technology are being investigated as a viable option for the future pixel tracker of the ATLAS experiment at the High-Luminosity LHC. This paper reports on the testbeam measurements performed at the H8 beamline of the CERN Super Proton Synchrotron on a High-Voltage CMOS sensor prototype produced in 180 nm AMS technology. Results in terms of tracking efficiency and timing performance, for different threshold and bias conditions, are shown.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…The telescope allowed the testing of various detectors, ranging from small and full size FE-I4 based sensors [12,13] to strip modules and pad detectors [14] read out by fully independent DAQ systems that were synchronised to the telescope by means of two trigger schemes. In the case of very small devices the Region Of Interest trigger speeded up data taking by a factor of 35 compared to triggering on the full telescope acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…The telescope allowed the testing of various detectors, ranging from small and full size FE-I4 based sensors [12,13] to strip modules and pad detectors [14] read out by fully independent DAQ systems that were synchronised to the telescope by means of two trigger schemes. In the case of very small devices the Region Of Interest trigger speeded up data taking by a factor of 35 compared to triggering on the full telescope acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…The proton irradiated sensors are directly glued and wirebonded to a printed-circuit-board (PCB). The neutron irradiated sensors are glued and wire-bonded to a ceramic carrier, which is connected to the same PCB type via a socket 3 . The PCB provides stable and ripple-free power, filters the high voltage and converts the differential slow control signals to single ended signals required by the MuPix7.…”
Section: Setupmentioning
confidence: 99%
“…For another sensor with a similar pixel cell design and hybrid readout (CCPDv4 [3]), it was shown that the analogue pixel performance remains high after particle fluences of up to 5.0 × 10 15 1 MeV n eq /cm 2 [4]. Additional studies with prototypes of Depleted Monolithic Active Pixel Sensor (DMAPS) based on a modified 180 nm CMOS process from TowerJazz [5] have also shown high efficiencies after irradition with up to 1 × 10 15 n eq /cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The AMS180v4 sensor has four kinds of pixel, and only the baseline one, STime pixel, was measured. The per-pixel analogue electronic of AMS180v4 comprises charge sensitive amplifiers, source followers and a discriminator stage which can be controlled by two voltage levels (global threshold from external and local threshold generated by the local DAC) [19]. The tuning procedure controls the 4-bit local DAC (named TDAC -Threshold DAC) connected to the discriminator of each pixel of the AMS180v4 sensor to compensate the possible local mismatches in the electronics between different pixels.…”
Section: Sensor Tuningmentioning
confidence: 99%